MODEL STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN PARIWISATA YANG BERBASIS KOMUNITAS LOKAL: KASUS DI KOTA PADANG PANJANG - Zulkarnain Harun (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
This paper discusses the Impact of Development of MIFAN, Padang Panjang to the socio-economic life of the community. This paper departs from the rising number of tourists coming to the Serambi Mekkah City, since the city to build an object Family Tourism namely MIFAN Waterpark. With the increase in tourist arrivals to Padang Panjang, namely attractions water and dry objects